Return connectedness of sectoral stock indices on the Indonesian stock exchange during Russian-Ukraine conflict - Fitriyah, Fitriyah; Mukminatin, Zakia Nur (Journal of Accounting and Investment, 2025)
Research aims: The purpose of this study is to determine the return connectedness of sectoral stock indices in Indonesia and to identify sectors that act as risk transmitters and risk recipients during the Russia-Ukraine conflict.Design/Methodology/Approach: The study employed a quantitative method with a comparative descriptive approach using data obtained from id.investing.com in the form of daily data on the closing price of the sectoral stock index starting from the period March 16, 2021 to March 14, 2023. The sampling technique used purposive sampling method. Time varying parameter VAR is an analytical tool used to analyze the data.Research findings: The test results found that the return connectedness of Sectoral Stock Indices increased during the Russia-Ukraine war. During the war, the sectoral indices that acted as risk transmitters were finance, industry, infrastructure, consumer cyclicals, and basic materials. Sectors that acted as risk receivers were health, transportation, energy, consumer non-cyclicals, and technology.Theoretical contribution/Originality: This is the first study to examine return spillover in Indonesia stock sectors, specifically focusing on the Russia-Ukraine conflict. This study provides understanding about return spillover and directional spillover among 11 Indonesian stock sectors.Practitioner/Policy implication: This article has important implications for investors to allocate their portfolios taking into account the similarities and differences in the time-varying connectivity characteristics of different asset systems. Also, for policymakers in Indonesia should adopt flexible regulatory strategies to avoid systemic risk contagion.